Arthroscopically assisted evaluation of frequency and patterns of meniscal tears in operative tibial plateau fractures: a retrospective study - Xiangtian Deng; Hongzhi Hu; Yuchuan Wang; Decheng Shao; Yingze Zhang (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Despite tibial plateau fractures are often associated with meniscal tears, the association between meniscal tears and Schatzker classification remains unclear. The purpose of this study was to assess the frequency and patterns of meniscal tears in operatively treated tibial plateau fractures following immediate arthroscopic evaluation after internal fixation of tibial plateau fractures and to reveal the association between these concomitant meniscal tears and Schatzker classification. Methods A total of 252 consecutive patients (166 males and 86 females, mean age 46.7 (19–80) years) with operatively treated tibial plateau fractures admitted to our hospital from January 2016 to May 2019 were performed. Arthroscopic examination for frequency and patterns of meniscal tears was evaluated and documented at the time of surgery, and the association between the frequency and patterns of meniscal tears with Schatzker classification was then analyzed. Results The overall frequency of meniscal tears in TPFs was 67% (168 of 252) with 33% (84 of 252) of these being lateral meniscal tears, and 10% (26 of 252) medial meniscal tears, while 23% (58 of 252) had bilateral meniscal tears. Schatzker II was most commonly associated with meniscal tears, occurring in 72% (71 of 99) of our series. There is no significant difference between the frequency of meniscal tears and Schatzker classification (p > 0.05). The most common patterns of meniscal tears were longitudinal tears in 23% of tibial plateau fractures (59 of 252), and it occurred at a significantly higher frequency in Schatzker II with 43% (43 of 99). Schatzker IV had significantly higher prevalence of bucket-handle tears than other fracture patterns (p < 0.05), and Schatzker VI fractures had significantly higher prevalence of complex tears than other fracture patterns (p < 0.05). For other Schatzker classification, the patterns of meniscal tears demonstrated no statistical difference (p > 0.05). Conclusion The results identified that meniscal tears are commonly seen in each Schatzker classification. Although various patterns of meniscal tears occurred in tibial plateau fractures, the most common patterns were longitudinal tears. Importantly, we suggest that the status of meniscal tears associated with TPFs should be considered at the time of surgery in addition to fracture fixation.